Optimization of rhodamine 123 adsorbed onto graphene oxide for tracing therapeutics processes. Issue 2 (7th February 2019) - Liao, Juan; Li, Lianwen; Yu, Haochen; Deng, Ao; Yuan, Zhaoxia
Abstract: The interaction between rhodamine 123 and graphene oxide in aqueous dispersion was examined by spectroscopic techniques. The quenching mechanism of rhodamine 123 adsorbed onto graphene oxide was static quenching. Rhodamine 123 and graphene oxide may form as a compound in the aqueous solution via π–π and electrostatic interactions. The fluorescence signal of rhodamine 123 adsorbed onto graphene oxide was changed in different pH solutions and culture mediums. The fluorescence signal of rhodamine 123 on graphene oxide was increased in the presence of 5% fetal bovine serum, but the increments kept constant between 5 and 25%. The concentration of cellular total protein may seriously affect the accuracy of the method. The fluorescence signal of cells incubated with graphene oxide was decreased in comparison with the one incubated in rhodamine 123 only. The method for observing cellular uptake and therapeutics releasing process could be recorded by fluorescence microscopy in the recommended condition.